Fast, low-cost preparation of hackmanite minerals with reversible photochromic behavior using a microwave-assisted structure-conversion method. Issue 53 (18th June 2018) - Carvalho, José M.; Norrbo, Isabella; Ando, Rômulo A.; Brito, Hermi F.; Fantini, Márcia C. A.; Lastusaari, Mika
Abstract : A microwave-assisted structure-conversion (MASC) method was used to obtain photochromic hackmanites (M, Na)8 Al6 Si6 O24 (Cl, S)2 (M: Li, Na, and K) in a fast (12 to 20 min) one-step process. Abstract : A microwave-assisted structure-conversion (MASC) method was used to obtain photochromic hackmanites (M, Na)8 Al6 Si6 O24 (Cl, S)2 (M: Li, Na, and K) in a fast (12 to 20 min) one-step process. Structural conversion from Zeolite A to hackmanite minerals has been proven to be very effective through an aluminosilicate crystalline intermediate. Photochromism is observed with both UV and X-ray (CuKα ) excitation.